Haemostatic Abnormalities Persist Despite Glycaemic Improvement by Insulin Therapy in Lean Type 2 Diabetic Patients - Knöbl, Paul; Schernthaner, Guntram; Schnack, Christoph; Pietschmann, Peter; Proidl, Sylvia; Prager, Rudolf; Vukovich, Thomas (Thrombosis and Haemostasis, 1994)
Diabetes mellitus is associated with disturbances of the haemostatic system, which might contribute to the development of diabetic vascular disease. We investigated the effect of metabolic improvement by insulin therapy on the haemostatic system in 61 patients with type 2 diabetes mellitus and secondaxy sulfunyluiea failure compared with 45 healthy control subjects matched for age, sex and BMI. Median age was 65, median diabetes duration 10 years. Median HbA1c (10%) and fructosamine (4.0 mM) levels were elevated before induction of therapy and decreased significantly within 6 months of insulin treatment to 7.5% and 3.0 mM, respectively (p <0.0001). Compared with control subjects, median plasma levels of fibrinogen (317 vs 286 mg/dl), coagulation factor VII activity (1.1 vs 0.89 U/1), von Willebrand factor (1.6 vs 1.3 U/1), D-dimer (105 vs 86 jug/1), protein C:Ag (1.24 vs 0.95 U/1), total protein S:Ag (1.15 vs 0.91 U/1), and antithrombin III activity (1.17 vs 1.08 U/1) were significantly elevated. Levels of free protein S were not different from control values. No significant decline of coagulation parameters could be recorded during insulin therapy. Patients with diabetic vasculopathy had higher levels of D-dimer than those without (133 vs 76 μg/1 before, 109 vs 88 μg/1 during therapy), whereas the other haemostatic parameters were not different. Our data indicate a significant activation of the coagulation system in diabetic patients with secondary failure to sulfonylurea drugs, with signs of a prethrombotic state and endothelial cell disturbance. Induction of insulin therapy results in a significant improvement of glycaemic and lipid metabolism, but the persisting enhanced activity state of the haemostatic system might contribute to the increased cardiovascular mortality of type 2 diabetic patients.